Implementing a tobacco-free workplace program at a substance use treatment center: a case study - Anastasia Rogova; Isabel Martinez Leal; Maggie Britton; Tzuan A. Chen; Lisa M. Lowenstein; Bryce Kyburz; Kathleen Casey; Kim Skeene; Teresa Williams; Lorraine R. Reitzel (BMC Health Services Research, 2024)
Abstract Background People with substance use disorders smoke cigarettes at much higher rates than the general population in the United States and are disproportionately affected by tobacco-related diseases. Many substance use treatment centers do not provide evidence-based tobacco cessation treatment or maintain comprehensive tobacco-free workplace policies. The goal of the current work is to identify barriers and facilitators to a successful and sustainable implementation of a tobacco-free workplace program, which includes a comprehensive tobacco-free policy and evidence-based cessation treatment services, in a substance use treatment center. Methods This study is based on an ethnographic approach and uses a qualitative case study design. Data were collected via interviews with staff (n = 6) and clients (n = 16) at the substance use treatment center and site visits (n = 8). Data were analyzed using thematic analysis guided by the extended Normalization Process Theory designed to inform the implementation of innovations in healthcare practice. Results Staff at the substance use treatment center supported the implementation of the program and shared a good understanding of the purpose of the intervention and its potential benefits. However, the study identified significant challenges faced by the center during implementation, including widespread tobacco use among clients, contributing to attitudes among staff that tobacco cessation was a low-priority problem due to a perceived lack of interest in quitting and inability to quit among their clients. We identified several factors that contributed to changing this attitude, including provision of tobacco training to staff, active leadership support, low number of staff members who smoked, and access to material resources, including nicotine replacement products. The implementation and active enforcement of a comprehensive tobacco-free workplace program contributed to a gradual change in attitudes and improved the provision of evidence-based tobacco cessation care at the substance use treatment center. Conclusions Substance use treatment centers can integrate tobacco cessation practices in their daily operations, despite multiple challenges they face due to the complex behavioral health and socioeconomic needs of their clients. With proper support, substance use treatment centers can provide much needed tobacco cessation care to their clients who are disproportionately affected by tobacco-related health conditions and systemic health inequities.